Mentoring for civil engineers - Waterhouse, Patrick (Civil engineer) (ICE Publishing, 2020)
'Mentoring for Civil Engineers' is a guide to planning and implementing the training of professional civil engineers. In an increasingly fast-moving industry, ensuring that engineers have the necessary skills, ability and commitment is key to success. Mentoring engineers is an important method to maintain performance in the workplace and this text offers practical guidance on how mentors can quickly motivate and inspire their trainees as they introduce them to the world of civil engineering and work towards their professional qualifications. It reveals hints and tips as well as best practice methods for supporting your trainee and for getting the best out of the mentor-trainee relationship.